(untitled) (VERUM: Journal of Scientific Initiation, 2025)
EDITORIAL TEAM EDITOR-IN-CHIEF Me. Ewerton da Silva Ferreira, Center for Interdisciplinary Studies, Brazil JUNIOR EDITOR Master’s Student Eduardo Lima, Federal University of Santa Catarina, Brazil TECHNICAL SUPPORT Bachelor Ricardo Macuglia, Center for Interdisciplinary Studies, Brazil Me. Tiara Cristiana Pimentel dos Santos, University of Passo Fundo, Brazil Bachelor Maria Fernanda Coffi Ávila, Federal University of Pampa, Brazil EDITORIAL BOARD Dr. Alan Dutra Melo – Federal University of Pampa, Brazil Dr. Cristóvão Domingos de Almeida – Federal University of Mato Grosso, Brazil Dr. Darlan De Mamann Marchi – Federal University of Pelotas, Brazil Dr. Juliani Borchardt da Silva – Federal University of the Southern Border, Brazil Dr. Léia Teixeira Lacerda – State University of Mato Grosso do Sul, Brazil Dr. Rogério Piva da Silva – Federal University of Rio Grande, Brazil Dr. Taniamara Vizzotto Chaves – Farroupilha Federal Institute of Education, Science and Technology, Brazil COVER DESIGN Eduardo Lima, Federal University of Santa Catarina, Brazil ABOUT THE JOURNAL VERUM: Journal of Scientific Initiation aims primarily to disseminate articles authored by undergraduate students alongside their academic advisors, especially those linked to scientific initiation programs. In doing so, it fosters exchanges between authors and readers to advance knowledge across various fields. VERUM publishes works stemming from the triad of Teaching, Research, and Extension on a rolling basis. Se quiser também a versão em espanhol, posso providenciar na sequência! Deseja isso?